2019
DOI: 10.1002/lary.28492
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of carboplatin via activating p53/miR‐145 axis in head and neck cancers

Abstract: In this study, we aimed at investigating the expressions of miR-145 and its well-characterized direct targets on carboplatin treatment. Study Design: Laboratory study. Methods: The effect of carboplatin and miR-145 on the proliferative capacity of head and neck squamous cell carcinoma cells was evaluated using Cell Viability Detection Kit-8. Expressions of miR-145 and its targets were evaluated using quantitative real-time polymerase chain reaction on carboplatin treatment and p53 inhibition. Western blot was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In tumors, miRs can either function as tumor suppressor gene or oncogene by regulating downstream targets. It is reported that miR-145 was down-regulated in nasopharyngeal carcinoma [26], papillary thyroid carcinoma [27] and head and neck cancers [28]. For example, Liu et al [26] reported that miR-145 directed with CASC9, and the inhibition of miR-145 promoted cell migration and invasion but inhibited cell apoptosis in nasopharyngeal carcinoma cells, which provided a novel therapy for the treatment of nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In tumors, miRs can either function as tumor suppressor gene or oncogene by regulating downstream targets. It is reported that miR-145 was down-regulated in nasopharyngeal carcinoma [26], papillary thyroid carcinoma [27] and head and neck cancers [28]. For example, Liu et al [26] reported that miR-145 directed with CASC9, and the inhibition of miR-145 promoted cell migration and invasion but inhibited cell apoptosis in nasopharyngeal carcinoma cells, which provided a novel therapy for the treatment of nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analyses and in vitro studies have shown that p53 is a potential regulator of mir‐145, which has a putative p53 response element in its promoter (Kilic et al, 2019; Sachdeva et al, 2009). Upregulation of endogenous p53 has been reported to increase mir‐145 expression and its promoter activity in cancer cells (Sachdeva et al, 2009), implying a critical role for miR‐145 after loss of p53 activity during carcinogenesis processes (Fuchs, 2012; Sachdeva et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are estimated to target and regulate the expression of about 60% of human genes (Shukla et al, 2011). They have been shown to be associated with the pathogenesis of various diseases including cancer, and can act as potential oncogenes or tumor suppressors, depending on the genes they are targeting (Kilic et al, 2019; Macharia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSC), an aggressive malignant neoplasm, is one of the most frequent cancers in the head and neck region with a global annual incidence of 700 000 cases 1‐3 . Lifestyle habits, genetic risk factors, tobacco use, alcohol consumption, poor oral hygiene, and high‐risk human papilloma virus (HPV) infection are among the prominent risk factors for HNSC 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSC), an aggressive malignant neoplasm, is one of the most frequent cancers in the head and neck region with a global annual incidence of 700 000 cases. [1][2][3] Lifestyle habits, genetic risk factors, tobacco use, alcohol consumption, poor oral hygiene, and high-risk human papilloma virus (HPV) infection are among the prominent risk factors for HNSC. 4,5 Despite improvements in the diagnostic and therapeutic modalities, there has been no remarkable increase in the overall survival rate of HNSC patients during the last few decades, 6 which is most probably due to the late stages at diagnosis and additional primary lesions.…”
Section: Introductionmentioning
confidence: 99%